(untitled) (Research, Society and Development, 2020)
Belonging to the Coronaviridae family, Sars-Cov-2 is an enveloped RNA virus that causes severe acute respiratory syndrome. As a preventive measure to the spread of the virus, the WHO suggests the application of quarantine and social isolation, which has been implicating in the quality of life, related to the psychological well-being of individuals, resulting in the appearance of stress, fear, anxiety, panic, guilt and sadness, as these signs reflect psychological distress and culminates in the emergence of psychosomatic disorders. This study aims to report the experience of nursing students in investigating the impacts of the Sars-Cov-2 pandemic and social isolation on people’s mental health. This is a study with a quantitative and qualitative approach, of the experience report type, developed in two stages, namely: 1 - data collection and 2 - results discussions. Data from the study reveal that 95.24% of the participants have or had negative feelings caused by social isolation, with concern being the feeling of greatest impact. In addition to this, there is also a state of excessive alertness and a lack of emotional control, which can be caused by the various negative news circulating in the media, distancing from family and friends, breaking the routine, in addition to fake news. Given the above, the need and importance to develop studies and health actions that will contribute to the promotion of emotional self-control, in order to guarantee a good quality of life in times of pandemic and social isolation, is evident.